STUDI PENDAHULUAN PENGAWETAN ROTAN BAHAN BAKU MEBEL - Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Rattan for the furniture raw materials is easily attacked by stain fungi and moulds during air drying, leaving discolored surfaces. The soft portion is also susceptible to attack of powder post beetles. To prevent this problem, the newly cut rattan should be treated with preservative to ensure a reasonable service life. The treatment method affects the extent of penetration and absorption of preservation into the rattan. The rasult of study on the preservation of rattan by pressure process is presented in this paper. A pressure period for 5, 15, and 25 minutas was sufficient to obtain required retention of preservative for the rattan tabu-tabu, batang and tohiti.